Inter-expert and intra-expert reliability in sleep spindle scoring. Issue 8 (August 2015) - Wendt, Sabrina L.; Welinder, Peter; Sorensen, Helge B.D.; Peppard, Paul E.; Jennum, Poul; Perona, Pietro; Mignot, Emmanuel; Warby, Simon C.
Highlights Spindle identification is a difficult task, and more than one sleep expert is needed to reliably score spindles in EEG data. The reliability of sleep staging may be improved by improving the reliability of spindle scoring, particularly for the discrimination of stage N1 and N2 sleep. Reliability of sleep spindle scoring can be improved by using qualitative confidence scores, rather than a dichotomous yes/no scoring system.